CD 120 wheat cultivar, standard quality soft, for the Southern Region of Brazil - Marchioro,Volmir Sergio (2011)
The cultivar CD 120, developed by the Cooperativa Central de Pesquisa Agrícola (COODETEC) is suitable for cultivation in the VCU wheat-producing regions 1 and 2 of the states of Paraná, Santa Catarina and Rio Grande do Sul. It is tolerant to the major wheat diseases and pre-harvest germination and has soft wheat quality and a 6.5 % higher grain yield (3.678 kg ha-1) than the control.